Comparative kinematic analysis of the snatch lifts in elite male adolescent weightlifters - Harbili, E.; Alptekin, A. (Journal of Sports Science & Medicine, 2014)
The purpose of the study was to compare the linear kinematics of the barbell and the angular kinematics of the lower limb during the snatch lifts of two different barbell weights in elite male adolescent weightlifters. In the national team level, nine elite male adolescent weightlifters participated in the study. The snatch lifts were recorded by two video cameras under competitive conditions in preparation period before the European Junior Championship (Sony MiniDv PAL- 50 field/s) and the two heaviest successful lifts were selected for kinematic analysis. The little toe, ankle, knee, hip, and shoulder on the body and one point on the barbell were digitized using Ariel Performance Analysis System (APAS, San Diego, CA, USA). Significant decreases were found in the maximum barbell height, the relative power output during the second pull, and the maximum vertical velocity of the barbell during the second pull of the heaviest lift (p < 0.05). Maximum extension velocity of the hip joint significantly increased during the first pull of the heaviest lift (p < 0.05). As the mass of the barbell increased, the maximum vertical velocity and the maximum height of the barbell and relative power output during the second pull decreased in the heaviest lift performed by adolescent weightlifters. Coaches should pay attention to assistant exercises to increase explosive strength during the second pull with maximum strength in male adolescent weightlifters.